Ginkgo biloba extract may alleviate viral myocarditis by suppression of S100A4 and MMP‐3. Issue 12 (9th August 2019) - Wang, Wei; Ma, Ke; Liu, Jiangtao; Li, Feng
Abstract: Viral myocarditis (VMC) is an inflammatory cardiac disease caused by coxsackievirus B3 (CVB3) that leads to heart failure or sudden death. However, efficient therapeutic strategies for VMC remain lacking. Ginkgo biloba extract was previously demonstrated to have anti‐inflammatory activity and had been used in prevention and therapy of some cardiovascular diseases (ie myocardial infarction), indicating Ginkgo biloba extract may be a potential drug for the treatment of VMC. This study was, for the first time, to investigate the intervention effects of Ginkgo biloba extract on VMC model mice and explore its potential mechanisms. As a result, VMC mice model was successfully established by CVB3 infection, exhibiting significantly higher viral titer, serum creatine kinase isoenzyme level, heart weight/body weight ratio, histopathologic scores, collagen volume fraction (CVF), and significantly increased expression of S100A4 and matrix metalloproteinase‐3 (MMP‐3) at protein and messenger RNA levels compared with the control group. Also, the expression of S100A4 and MMP‐3/CVF was positively correlated. Ginkgo biloba extract treatment significantly reversed the trend in all the above parameters. Thus, Ginkgo biloba extract may be a promising therapeutic approach against VMC because it improved myocardial injury and alleviated the degree of myocardial fibrosis through suppression of S100A4 and MMP‐3. Highlight: Ginkgo biloba extract is effective for treatment of viral myocarditis. Ginkgo biloba extract improves myocardial injury via regulating S100A4 and MMP‐3. S100A4 and MMP‐3 is positively correlated in viral myocarditis.